The Short Form of the Zinc Finger Antiviral Protein Inhibits Influenza A Virus Protein Expression and Is Antagonized by the Virus-Encoded NS1 - Tang, Qiannan (J Virol, 2017)
Zinc finger antiviral protein (ZAP) is a host factor that specifically inhibits the replication of certain viruses. There are two ZAP isoforms arising from alternative splicing, which differ only at the C termini. It was recently reported that the long isoform (ZAPL) promotes proteasomal degradation of influenza A virus (IAV) proteins PA and PB2 through the C-terminal poly(ADP-ribose) polymerase (PARP) domain, which is missing in the short form (ZAPS), and that this antiviral activity is antagonized by the viral protein PB1. Here, we report that ZAP inhibits IAV protein expression in a PARP domain-independent manner. Overexpression of ZAPS inhibited the expression of PA, PB2, and neuraminidase (NA), and downregulation of the endogenous ZAPS enhanced their expression. We show that ZAPS inhibited PB2 protein expression by reducing the encoding viral mRNA levels and repressing its translation. However, downregulation of ZAPS only modestly enhanced the early stage of viral replication. We provide evidence showing that the antiviral activity of ZAPS is antagonized by the viral protein NS1. A recombinant IAV carrying an NS1 mutant that lost the ZAPS-antagonizing activity replicated better in ZAPS-deficient cells. We further provide evidence suggesting that NS1 antagonizes ZAPS by inhibiting its binding to target mRNA. These results uncover a distinct mechanism underlying the interactions between ZAP and IAV. IMPORTANCE ZAP is a host antiviral factor that has been extensively reported to inhibit the replication of certain viruses by repressing the translation and promoting the degradation of the viral mRNAs. There are two ZAP isoforms, ZAPL and ZAPS. ZAPL was recently reported to promote IAV protein degradation through the PARP domain. Whether ZAPS, which lacks the PARP domain, inhibits IAV and the underlying mechanisms remained to be determined. Here, we show that ZAPS posttranscriptionally inhibits IAV protein expression. This antiviral activity of ZAP is antagonized by the viral protein NS1. The fact that ZAP uses two distinct mechanisms to inhibit IAV infection and that the virus evolved different antagonists suggests an important role of ZAP in the host effort to control IAV infection and the importance of the threat of ZAP to the virus. The results reported here help us to comprehensively understand the interactions between ZAP and IAV.